2020
DOI: 10.1007/s00148-019-00764-3
|View full text |Cite
|
Sign up to set email alerts
|

The importance of being earliest: birth order and educational outcomes along the socioeconomic ladder in Mexico

Abstract: We study the effect of birth order on educational outcomes in Mexico using 2 million observations from the 2010 Census. We find that the effect of birth order is negative, and a variety of endogeneity and robustness checks suggest a causal interpretation of this finding. We then examine whether these effects vary across households' economic status, and we find significant heterogeneity across absolute as well as relative standards of living, operationalized as household wealth and relative deprivation. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 95 publications
0
24
0
Order By: Relevance
“…Previous researchers have suggested that birth order is a result of the educational process and varies. Birth order does not entirely affect students' academics (Esposito et al, 2020).…”
Section: Figure 2 Order Of Birth Of Respondentsmentioning
confidence: 96%
“…Previous researchers have suggested that birth order is a result of the educational process and varies. Birth order does not entirely affect students' academics (Esposito et al, 2020).…”
Section: Figure 2 Order Of Birth Of Respondentsmentioning
confidence: 96%
“…They argue that high poverty rates in Ecuador or in developing countries more generally could be an explanation for this opposite finding. A recent paper by Esposito et al (2020) using data from Mexico, a middle-income country but with an array of features typical of low-income countries, finds a negative correlation between birth order and education. They rely on Census data and their results shed light onto the existence of economic gradients in birth order effects when we compare results from different countries.…”
Section: Literaturementioning
confidence: 99%
“…It is well established in the literature that earlier borns tend to have more years of education than laterborns (Becker and Lewis 1973;Behrman and Taubman 1986;Black et al 2005a;De Haan 2010;Mechoulan and Wolff 2015;Monfardini and See 2016;Esposito et al 2020).…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have focused on the relationship of birth order to intelligence, career choices, and success in adulthood (15). Also, it has been reported that first-borns often choose occupations that require high precision, such as academic, medical, law, engineering, computer, or accounting careers (15,16).…”
Section: Introductionmentioning
confidence: 99%